Relevansi Pelembagaan Investasi Ekonomi Berbasis Shariah Pada Masyarakat Muslim di Mindanao - Surwandono, Surwandono (Jurnal Hubungan Internasional, 2015)
The idea of building shariah economic investment institution was pioneered by Muhammadiyah when involved in the International Contact Group (ICG) to strengthening civil capacity of the muslim mindanao community through the transformation of social, economy, and education, as the initation of Baitul Mal Wa Tamwil establishment, as the embryo of economic shariah investment institution. This article will build a new idea which in the community who experiencing conflict still need shariah economic investment institution. Institute of shariah economic will guide the choice toward politic and military confrontation to more moderate and measureable in the community, which is in the end will contributes positively in creating peace.